Nondestructive evaluation of metal contaminated silicon wafers using radiometric measurements - Kalli, Kyriacos; Christofidès, Constantinos; Othonos, Andreas S.; Tardiff, F. (My University, 1999)
Metal contaminated silicon wafers were examined using nondestructive methods based on photothermal radiometry. This approach relies on measuring the blackbody radiation emitted from a material excited by a modulated laser source. Information is recovered regarding the electronic and thermal properties of the semiconductor as a function of laser modulation frequency. Data collected as a function of modulation frequency and time show clear distinctions between different samples. The sensitivity to different forms of metallic contamination is examined.
Keywords: Semiconductor doping; Silicon; Surface contamination; Nondestructive testing; Photothermal spectroscopy